VAR models with fat tails and dynamic asymmetry - Tamás Kiss; Stepan Mazur; Hoang Nguyen; Pär Österholm (Örebro University School of Business, 2024)
In this paper, we extend the standard Gaussian stochastic-volatility Bayesian VAR by employing the generalized hyperbolic skew Student's t distribution for the innovations. Allowing the skewness parameter to vary over time, our specification permits flexible modelling of innovations in terms of both fat tails and - potentially dynamic - asymmetry. In an empirical application using US data on industrial production, consumer prices and economic policy uncertainty, we find support - although to a moderate extent - for time-varying skewness. In addition, we find that shocks to economic policy uncertainty have a negative effect on both industrial production growth and CPI inflation.
Keywords: C11; C32; C52; E44; E47; G17; 330; Bayesian VAR; Generalized hyperbolic skew Students's t distribution; Stochastic volatility; Economic policy uncertainty